The Influence of Self-Generated and Third-Party Claims Online: Perceived Self-Interest as an Explanatory Mechanism. Issue 5 (9th July 2019) - DeAndrea, David C; Vendemia, Megan A
Abstract: Over the past two decades, communication technology scholars have examined how viewers evaluate the authenticity of information online, with particular attention given to how self versus third-party claims differ in their degree of influence. We examine how self-interest perceptions serve an important explanatory function in the logic of warranting theory and help account for how people evaluate content online. Our results document how the source and valence of a message can interact to affect perceptions of source self-interest, which, in turn, affect perceptions of source trustworthiness, message accuracy, and, ultimately, evaluations of an online target. The findings establish boundary conditions for the warranting principle and our discussion offers insight into the production and evaluation of online claims.